Strategi Pemulihan EKonomi Masyarakat Setelah Pandemi Covid-19 : Waena Kampung, Distrik Heram, Kota Jayapura - Daniel Ayub Dawan; Numberi (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2022)
Of course, there is close contact with institutions when it comes to the actions carried out; the institutions at issue are the Covid 19 Epidemic Handling and Prevention Task Force and the Jayapura City Health Office. This is because the activity will be a strategy to increase community participation in COVID-19 prevention efforts in Waena Village, Heram District, Jayapura City. Aside from that, the team did not define the intended criterion, which would be altered in light of the COVID-19 outbreak. The indications for meeting the goals are, first and foremost, complying with the government's request and the COVID-19 preventive task force team by following health standards, including 1. rigorously wearing masks when undertaking activities outside the home. When performing activities or events outside the home, keep your distance. 3. Completely wash your hands before and after performing tasks inside and outside the home. All of this is done to safeguard the residents of Waena Village from the COVID-19 infection. Second, the government really aspires to community involvement in COVID-19 prevention activities in Waena Village, Heram District. One of the greatest options is to follow the advice of the government and the COVID-19 preventive task force team by establishing health measures. The author expects success based on the community's concern and engagement in COVID-19 prevention, which is extremely excellent, and the output accomplished by the people of Waena village until March 2021, when there will be no more people infected with COVID 19.